Overview of Imaging Modalities in Evaluation of Bone Allograft Viability - Meena, Anjali; Dhingra, Mohit; K Dhingra, Vandana (Journal of Radiation and Nuclear Medicine, 2021)
The goal of this review is to assess the importance of various imaging modalities which can be used in assessing the viability and integrity of the bone allograft. As it is widely in use in majority of major and minor reconstructive procedures.
Keywords: Bone allograft; viability; graft materials; SPECT/CT; bone healing; Xray; MRI